Uji Daya Hasil Galur F6 Tanaman Kedelai (Glycine max L. Merrill) Hasil Persilangan Grobogan Dengan Km 19 - Ahmad Faidullah HN; Aslim Rasyad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
1.2. The purpose of this research is to determine some potential lines to be continued with the preliminary yield trial. The Lines used obtained from selected F3 plants resulted from a cross between Grobogan and KM19 having large seed and early maturity. Thirteen genotypes, consisting of the 11 F6 lines and two parents namely Grobogan and KM19 were planted in the Experimental Station of the Faculty of Agriculture, University of Riau, Pekanbaru. Field experiments were established by using a randomized block design in a 3 m x 2 m plot with three replications. Plant materials were maintened according to standard cultivation techniques and spacing of 40 cm x 20 cm. The parameters observed included plant height, number of branches, age of flowering, age of harvest, number of filled per plant, number of seeds per plant, weight of seeds per plant, weight of 100 seeds, dry weight of plants, and yield per m2. The data were analyzed according to the Dunnet test at the 5% level by the SAS Program version 9.0. The results indicated wide variability between lines for seed number per plant, seed weight per plant, and seed yield per m2. Genetic component of variance was greater than 0 for the three characters with high heritability. There were detected several linesw having high yield potential; ie, GK19-3-12, GK19-3-27 and GK19-3-41 with greater number of filled pods, higher seeds weight per plant and seed weight per m2than Grobogan and KM19. Keywords : genetic variance, heritability, yield potentials, yield components